Modernizing Tradition : Gender and Consumerism in Interwar France and Germany - Stanley, Adam C., 1974- (Book collections on Project MUSE., 2008)
In the turbulent decades after World War I, both France and Germany sought to return to an idealized, prewar past. Many people believed they could recapture a sense of order and stability by reinstituting traditional gender roles, which the war had thrown off balance. While French and German women necessarily filled men's roles in factories and other jobs during the war, those who continued to lead active working lives after World War I risked being called "modern women." Far from a compliment, this derogatory label encompassed everything society found threatening about women's new p.